2015
DOI: 10.1111/1467-8551.12099
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on the Map: An Exploration of Strategic Sensemaking/Giving Practices using Visual Representations

Abstract: In this paper we explain how practitioners perform strategic sensemaking with visual representations. Here, we identify four modes of strategic sensemaking/giving: contentgenerating, process-generating, process-ingraining and content-ingraining. While each of these modes supports strategic sensemaking/giving by focusing practitioners' work on specific issues, they also divert practitioners from focusing on key aspects of strategy making. We conceptualize these limitations as 'blind spots'. As a result, strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 63 publications
0
31
0
2
Order By: Relevance
“…Likewise, Groleau et al (2012) observe architects using visual representations over a six-month period, two days a week, with particular attention to how an intern used 3D software. Others focus on visual representations in meetings: Garreau et al (2015) accessed these through a business office acting as development client, and Ewenstein and Whyte (2009) through an architectural firm. There is a growing use of video ethnography as a way of capturing even richer and more detailed data on social interaction in design and organizational practices (LeBaron and Whittington, 2009;Smets et al, 2014).…”
Section: Theoretical Background and Current Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Groleau et al (2012) observe architects using visual representations over a six-month period, two days a week, with particular attention to how an intern used 3D software. Others focus on visual representations in meetings: Garreau et al (2015) accessed these through a business office acting as development client, and Ewenstein and Whyte (2009) through an architectural firm. There is a growing use of video ethnography as a way of capturing even richer and more detailed data on social interaction in design and organizational practices (LeBaron and Whittington, 2009;Smets et al, 2014).…”
Section: Theoretical Background and Current Approachesmentioning
confidence: 99%
“…First, through the discussion of these two studies, we offer an alternative approach that supplements situated ethnographies of design practices (e.g. Yaneva, 2009;Groleau, Demers et al, 2012;Garreau, Mouricou et al, 2015;Ewenstein and Whyte, 2009). Rather than assuming that action unfolds where the observation takes place (Czarniawska, 2007), our ethnographic approach allows the researcher to be nimble, tracing connections across engineering projects through visual representations.…”
Section: Concluding Remarks: Tracing Connections Using Visual Represementioning
confidence: 99%
“…Visual methods for the mapping of social networks form part of an emerging dialogical approach to visual data in management research (Garreau, Mouricou and Grimand, ; Vince and Warren, ). They are related to established techniques for cognitive mapping (Geiger and Finch, ; Ramos and Ford, ; Swan, ).…”
Section: Visual Network Researchmentioning
confidence: 99%
“…In contrast, an emerging stream of research, borrowing from the practice turn in strategic management, has observed the way strategic sensemaking actually unfolds, without making assumption as to whose meaning matters the most. This stream is less concerned with what meaning is reached, and focuses more on how conversations and other practices bring about meaning during strategic change (e.g., Cooren et al, 2015;Garreau et al, 2015), including through sensegiving (Balogun et al, 2014). This research attitude has allowed recognizing that sensemaking is a cooperative achievement that may implicate an array of organizational members and that may result in the adoption of fragmented interpretations that result from multidirectional relationships (e.g., Ritella & Ligorio, 2016;Tao & Tombros, 2017).…”
Section: What Is (Strategic) Sensemaking?mentioning
confidence: 99%